Induction of the 47 kDa platelet substrate of protein kinase C during differentiation of HL-60 cells. - Tyers, M (1987)
Immunoblot analysis showed that the 47 kDa platelet substrate of protein kinase C (P47) was expressed at low levels in undifferentiated HL-60 leukaemia cells. Treatment of these cells with dimethyl sulphoxide, 1 alpha,25-dihydroxycholecalciferol or retinoic acid caused progressive increases in P47 content. Retinoic acid (1 microM) elicited the largest response, a 4-fold increase in P47 protein after 7 days that was accompanied by an increase in translatable P47 mRNA. The induction of P47 by retinoic acid preceded cessation of cell proliferation and development of the capacity to reduce Nitro Blue Tetrazolium, indicating that its expression is an early event in the myeloid differentiation of HL-60 cells.